2016
DOI: 10.3389/fcimb.2015.00101
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of Innate Immune Responses by the Highly Virulent Cryptococcus gattii by Altering Capsule Glucuronoxylomannan Structure

Abstract: Cryptococcus neoformans causes life-threatening diseases mainly in immunosuppressed hosts such as AIDS patients; C. gattii causes disseminated infections even in healthy hosts. To identify the possible molecular mechanisms underlying this difference in virulence, we investigated the survival and histopathology of lung tissue in wild-type and CD4-depleted mice infected with C. neoformans H99 and C. gattii JP02 (the highly virulent strain isolated in Japan); we then compared dendritic cell (DC) cytokine release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 35 publications
0
65
2
Order By: Relevance
“…63,64 In the periphery, the capsular polysaccharide can interfere with phagocytosis, antigen presentation, leukocyte migration and proliferation, and specific antibody responses, and can enhance HIV replication. 65,66 Alternatively, the black pigment melanin may play a role in anti-phagocytic activity of C. neoformans. 67 In avirulent nonmelanogenic C. neoformans infected mice produced numerous key cytokines as described above without fatality, the virulent melanogenic fungi produces little or no cytokine secretion in mice with massive tissue damage and a number of fatalities.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…63,64 In the periphery, the capsular polysaccharide can interfere with phagocytosis, antigen presentation, leukocyte migration and proliferation, and specific antibody responses, and can enhance HIV replication. 65,66 Alternatively, the black pigment melanin may play a role in anti-phagocytic activity of C. neoformans. 67 In avirulent nonmelanogenic C. neoformans infected mice produced numerous key cytokines as described above without fatality, the virulent melanogenic fungi produces little or no cytokine secretion in mice with massive tissue damage and a number of fatalities.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…The cryptococcal capsule, one of the major virulence factors of Cryptococcus, is mainly composed of glucuronoxylomannan (GXM), which has several immunomodulatory properties (9,19). However, it has been reported that the GXM capsule structure of C. gattii strains differs from that of C. neoformans strains and may be responsible for the different degrees of host activation (20) associated with the two species complexes. Urease is another major virulence factor shared by both species complexes and one that is proposed to have several roles, though these remain under debate (21).…”
mentioning
confidence: 99%
“…Intriguingly, a recent transcriptomics study identified CAS31 as being absent from the genome of strain CBS 10101, a serotype C isolate that we subsequently found was not recognised by Crp127. Whilst we cannot rule out the possibility that other factors contribute to the inability of Crp127 to recognise serotype C strains, it is tempting to speculate that the loss of CAS31 function in this lineage may explain its lack of reactivity with Crp127 (32, 34).…”
Section: Discussionmentioning
confidence: 91%
“…Whilst there is no consensus surrounding the effect of GXM O -acetylation on virulence (17, 32), its influence on antibody binding suggests that changes in GXM O -acetylation could be a strategy deployed by cryptococci to avoid recognition by immune effectors. Additionally, despite the immunomodulatory roles for GXM O -acetylation that have been identified (30, 33), receptors that bind O -acetylated GXM remain elusive (34). Due to the enigmatic nature of this modification within the primary virulence factor of cryptococci, further investigation of GXM O -acetylation will help unravel the complexities of cryptococcal capsule structure with the ultimate aim of understanding the strategies deployed by this fatal fungal pathogen to evade host immunity.…”
Section: Introductionmentioning
confidence: 99%